Analisis Pembentukan Portofolio Yang Efisien Dengan Model Markowitz Pada Perusahaan Asuransi Di Indonesia. - Setiawan, Andika, Dra. Wafiatun Mukharomah, M.M (2015)
The purpose of this study was to determine how the level of profit expected from each portfolio composition and risk of the each composition and determines the composition of the portfolio which can form an efficient portfolio. The formation of the portfolio by Markowitz model is one model that can be used to form an efficient portfolio. The sampling technique in this study using purposive sampling so that the sample used in this study is AMAG, AHAP, ASRM and ASJT. Data analysis techniques used in this study is the return (profit rate), expected return (expected profit rate), standard deviation and variance (level of risk, correlation coefficient (degree of closeness of the relationship between variables), the expected return on the portfolio and the portfolio risk. Based on calculations that have been done, it can be concluded that an efficient portfolio is a portfolio of stocks between ASRM ASJT 60% and 40% can be selected as an efficient portfolio amounted to 2.54% with a risk of 18.24%. Because it has the advantage of 1.14 time to 1.03 time the risk level of the portfolio between AHAP combination of shares and ASJT.